Hifomicetos ingoldianos del río Frío (Floridablanca), Santander, Colombia (2016)
The diversity of Ingoldian hyphomycetes in Colombia is known from three studies that reported in total 18 species of these fungi. For eastern Colombian there are no records of these microorganisms. In this study foam samples were collected in the Frio River drainage in the municipality of Floridablanca (Santander) in October 2013 and September 2014. In this inventory 23 hyphomycetes taxa are reported of which 20 are new records for Colombia. Clavatospora tentacula was found in both sample periods. A marked decline in species richness related to the reduction of rainfall in the year 2014 was observed.